Salmonella enterica subspecies enterica serovar Choleraesuis in a German wild boar population: occurrence and characterisation - Ulrich Methner; Sabine Merbach; Martin Peters (Acta Veterinaria Scandinavica, 2018)
Abstract Background The swine-adapted serovar Choleraesuis of Salmonella enterica subspecies enterica is found rarely in domestic pigs in Germany. However, a considerable and increasing number of S. Choleraesuis organisms have been isolated from wild boars in Germany in recent years. To investigate a possible epidemiological context, S. Choleraesuis strains from a regional German wild boar population and other hosts were characterised by genotyping methods. Results Macrorestriction analysis, biochemical differentiation and antimicrobial susceptibility typing enabled the identification of several clusters of S. Choleraesuis. Some clusters occurred almost permanently in a certain district, whereas other groups circulated among different wild boar herds in larger regions. Non-porcine hosts were infected with the same cluster as the wild boars. Conclusions The emergence of S. Choleraesuis in wild boars might be caused by a higher prevalence in the wild boar population, but also the higher awareness to infections with African swine fever may have resulted in a higher number of examined animals. Separation of wild boar populations and, as a result, also the diverse S. Choleraesuis organisms might be due to natural barriers and artificial barriers like arterial roads. The findings of S. Choleraesuis in domestic pigs emphasize the importance of strict biosecurity measures to prevent transmission from wild boars of this but also other pathogens. To avoid risks for humans by zoonotic pathogens regular inspections of meat from wildlife need to be conducted.